DESIGNER’S PERSONAL BRAND: FORMING AN INFORMATION MODEL - Tserkovna, Oksana (Theory and practice of design, 2025)
The article is devoted to the study of the designer’s personal brand as a holistic information system that forms the identity of a specialist in the visual and professional environment. The purpose of the study is to develop an information model of the designer’s personal brand, which is based on the parametric method of normalization. Methodology. The research methods are based on an interdisciplinary approach that combines the methods of system analysis, branding, graphic design, as well as parametric normalization. Results. The study rethought the process of forming a designer’s personal brand; as a result, an information model was created and substantiated that reveals the brand as a multi-level dynamic system. The model combines fixed structural elements (identification, semantic, functional) and variable parameters (interactive, communicative), ensuring adaptability to the context and audience. Scientific novelty. The proposed model allows designers to: understand a personal brand as a tool for self-presentation, professional implementation and strategic communication with the audience; identify key stages of brand formation, starting from identification and semantic content, and ending with means of interaction and evaluation of effectiveness; ensure flexibility and scalability of the brand, which is especially relevant for young professionals at the beginning of their career; contributes to the development of personal style, increased recognition and positioning in the professional environment; allows you to evaluate the results of communication with the audience using such parameters as engagement, loyalty, citations and the number of orders. Practical relevance. The constructed information model opens up new opportunities for strategic management of a designer’s personal brand, meeting the modern challenges of the creative industry and contributing to the professional self-affirmation of young professionals.